Glomerular Filtration Rates in Asians - Teo, Boon Wee (Archīum Ateneo, 2018)
The National Kidney Foundation Kidney Disease Outcomes Quality Initiative guidelines recommended the Modification of Diet in Renal Disease study equation for estimating glomerular filtration rate (GFR) for the classification of CKD, but its accuracy was limited to North American patients with estimated GFR /min per 1.73 m2 body surface area of European (White) or African (Black) descent. The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) developed another equation for estimating GFR, derived from a population that included both participants without kidney disease and with CKD. But many ethnicities were inadequately represented. The International Society of Nephrology, Kidney Disease Improving Global Outcomes committee promulgated clinical practice guidelines, which recommended the CKD-EPI equation. Investigators in Asia subsequently assessed the performance of these GFR estimating equations—the Modification of Diet in Renal Disease study equation, the CKD-EPI equation (creatinine only), and the CKD-EPI equations (creatinine and cystatin C). In this review, we summarize the studies performed in Asia on validating or establishing new Asian ethnicity GFR estimating equations. We included both prospective and retrospective studies which used serum markers traceable to reference materials and focused the review of the performance of GFR estimation by comparisons with the GFR estimations obtained from the CKD-EPI equations.